Comparison of use of the Dalkon Shield in Dublin and Southampton. Issue 5971 (14th June 1975) - Miller, J F; Snowden, R; Loughran, J T; Elstein, M
Abstract : The results of fitting Dalkon Shield I.U.D.s in Southampton and Dublin were compared. At 12 months the continuation rates were 77.4% and 93.4% respectively. There were also differences between the two cities in the major complication rates associated with the use of the device. At 12 months these rates for Southampton and Dublin were: pregnancy 5.6% and 1.4%, expulsion 4.0% and 0.9%, and removal for pain and/or bleeding 12.1% and 3.0%, respectively. Possible reasons for the difference in performance may include the older average age of the users in Dublin, and the greater number and more varied experience of the medical staff responsible for fitting in Southampton. We recommend that population factors be taken into account when comparing data relating to fertility regulation.